Human Milk Fat Substitutes Containing Omega-3 Fatty Acids - Sahín, Nese; Akoh, Casimir C.; Karaalí, Artemis (American Chemical Society (ACS), 2006)
Structured lipids resembling human milk fat (HMF) enriched with omega-3 fatty acids were synthesized by enzymatic acidolysis reactions between tripalmitin, hazelnut oil fatty acids (FA), and omega-3 FA concentrate. Response surface methodology was used to model and optimize the incorporation of omega-3 FA and oleic acid into tripalmitin, in hexane, using immobilized sn-1,3-specific lipase, Lipozyme RM IM. The three factors chosen were substrate molar ratio, reaction temperature, and reaction time. Good quadratic models were obtained for the incorporation of eicosapentaenoic acid (EPA) plus docosahexaenoic acid (DHA) (response 1) and oleic acid (response 2) by multiple regression and backward elimination. The determination coefficient (R2) value for the models was 0.95. The adjusted R2 values were 0.91 and 0.92 for responses 1 and 2, respectively. The optimal conditions generated from the models for the targeted total EPA and DHA (5%) and oleic acid (40%) incorporation were 12.4 mol/mol, 55 degrees C, and 24 h for substrate ratio, temperature, and time, respectively. The model was verified, which led to the production of a HMF ingredient with 76.6% palmitic acid at the sn-2 position.
Keywords: Analysis of Variance; Docosahexaenoic Acids; Milk, Human; Infant, Newborn; Palmitic Acid; Lipase; Infant Formula; Corylus; Fish Oils; Eicosapentaenoic Acid; Fatty Acids, Omega-3; Humans; Plant Oils; Female; Fat Substitutes; Triglycerides; Oleic Acid